(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Virudhahara, or incompatible food, is a foundational concept in Ayurveda that refers to food combinations or preparations which disturb the equilibrium of the Doshas but do not facilitate their elimination, thereby leading to the accumulation of toxins (Ama) and the onset of disease. This paper explores the concept of Virudhahara in the context of rising global consumption of junk food. Junk foods, characterized by high levels of sugar, salt, unhealthy fats, preservatives, and low nutritional value mirror many types of dietary incompatibilities described in Ayurvedic texts, such as Agni Virudha (incompatibility with digestive fire), Samyoga Virudha (wrong food combinations), Samskara Virudha (improper food processing), and Satmya Virudha (incompatibility with one’s habit or constitution). The study conducts a critical review of Ayurvedic classical references and correlates them with contemporary definitions and harmful effects of junk food consumption. It discusses the physiological mechanisms through which Virudhahara leads to Agnimandya, Ama formation, Srothorodha, and eventual manifestation of systemic disorders such as obesity, diabetes, cardiovascular disease, neurological conditions, and even cancer. The review also identifies factors that can mitigate the effects of Virudhahara and outlines classical Ayurvedic treatments like Shodhana (purification), Shamana (palliative therapies), and Rasayana (rejuvenation). By drawing parallels between ancient Ayurvedic wisdom and modern dietary trends, this paper emphasizes the urgent need to re-evaluate current eating habits and adopt preventive strategies rooted in traditional health science.